Striking a balance between aesthetics and safety: a comparative study on the maternal and neonatal outcomes of mini-incision cesarean section - ChunLan Yuan; ShiMei He; WenQian Jian; MeiRong He; HuiFang Huang; JianChun Huang; MeiPing He; KaiSun Zhao (BMC Pregnancy and Childbirth)
Abstract Objective and significance The pursuit of aesthetic outcomes is a natural tendency for individuals, particularly for women undergoing cesarean sections, who seek to minimize abdominal scarring. The aim of this study is to compare the risks and outcomes of mini-incision cesarean sections with those of conventional incision cesarean sections. Methods A total of 99 pregnant women with full-term singleton pregnancies, who delivered at the Second Nanning People's Hospital from January 2024 to September 2024, were enrolled in this study. The participants were stratified into two groups: the mini-incision group (n = 33) and the conventional incision group (n = 66). The study evaluated several variables, including the time from incision to fetal delivery (I-D), surgery duration, intraoperative blood loss, duration of postoperative antibiotic administration, post-operative hospitalization duration, incidence of wound infection, neonatal adverse outcomes, and blood routine parameters. Results The surgery duration in the mini-incision group was significantly shorter than that in the conventional group. Furthermore, the rate of forceps-assisted delivery was significantly higher in the mini-incision group (P < 0.05 for both comparisons). However, no statistically significant differences were observed between the two groups in terms of intraoperative blood loss or maternal and neonatal outcomes, including neonatal complications, incidence of wound infection, and other maternal outcomes. Conclusion Our findings indicate that when a pregnant woman requests a mini-incision cesarean section, the procedure can be safely performed by an experienced obstetrician proficient in forceps-assisted delivery techniques, provided it is not categorized as a Category I cesarean section.